Alternative oxidase mediates pathogen resistance in Paracoccidioides brasiliensis infection. - Orville Hernández Ruiz; Angel Gonzalez; Agostinho J Almeida; Diana Tamayo; Ana Maria Garcia; Angela Restrepo; Juan G McEwen (Public Library of Science (PLoS), 2011)
Background Paracoccidioides brasiliensis is a human thermal dimorphic pathogenic fungus. Survival of P. brasiliensis inside the host depends on the adaptation of this fungal pathogen to different conditions, namely oxidative stress imposed by immune cells. Aims and methodology In this study, we evaluated the role of alternative oxidase (AOX), an enzyme involved in the intracellular redox balancing, during host-P. brasiliensis interaction. We generated a mitotically stable P. brasiliensis AOX (PbAOX) antisense RNA (aRNA) strain with a 70% reduction in gene expression. We evaluated the relevance of PbAOX during interaction of conidia and yeast cells with IFN-γ activated alveolar macrophages and in a mouse model of infection. Additionally, we determined the fungal cell's viability and PbAOX in the presence of H₂O₂. Results Interaction with IFN-γ activated alveolar macrophages induced higher levels of PbAOX gene expression in PbWt conidia than PbWt yeast cells. PbAOX-aRNA conidia and yeast cells had decreased viability after interaction with macrophages. Moreover, in a mouse model of infection, we showed that absence of wild-type levels of PbAOX in P. brasiliensis results in a reduced fungal burden in lungs at weeks 8 and 24 post-challenge and an increased survival rate. In the presence of H₂O₂, we observed that PbWt yeast cells increased PbAOX expression and presented a higher viability in comparison with PbAOX-aRNA yeast cells. Conclusions These data further support the hypothesis that PbAOX is important in the fungal defense against oxidative stress imposed by immune cells and is relevant in the virulence of P. brasiliensis.